Adaptation of Multi Walled Carbon Nanotubes on Viscoelastic and Damping Behavior of Flax Fiber Composite. Issue 16 (28th November 2022) - Rajendran, Balaji; P K, Dinesh Kumar; S, Devaganesh; Venkateshwaran, N
ABSTRACT: Damping characteristics and viscoelastic behavior of flax/epoxy composites reinforced with carboxyl-functionalized multi-walled carbon nanotubes (COOH-MWCNT) were investigated in this study. The viscoelastic behavior was studied utilizing dynamic mechanical analysis (DMA), conducted on all the fabricated composite specimens and neat-resin (pure epoxy). The results revealed an improvement in glass transition temperature ( T g ) for flax epoxy composites with 0 wt.%, 0.5 wt.%, and 1 wt.% reinforcement of MWCNT when compared to the free-resin. From the obtained graphs, C-factor was estimated, adhesion factor and Cole–Cole plots were drawn. The frequency response function (FRF) plot, obtained from free vibration testing, unveils the natural frequencies at mode-I and mode-II vibration, and their respective damping ratios are estimated by half-power bandwidth method. The damping ratios and the natural frequencies increased with the addition of MWCNT. The flax/epoxy composite reinforced with 1 wt.% of MWCNT was found to prevail over the rest by exposing great vibration damping, viscoelastic and mechanical properties.